COVID-19: viral characterization, pathophysiology and prevention (Research, Society and Development, 2020)
Introduction: There are seven known species of human coronavirus capable of causing respiratory diseases. The most recent is SARS-CoV-2, the etiologic agent of COVID-19. Objective: To evaluate the main characteristics of SARS-CoV-2, the pathophysiology of COVID-19 and the main measures for prevention and containment of disease progression. Methods: An integrative review was carried out between 2003 and 2020, based on: PubMed, Medline, SciELO, LILACS and Google Academic, using the descriptors: COVID-19, coronavirus, novel coronavirus, human, SARS virus, outbreak disease, viral pneumonia, all listed in MESH and DECS. Results: Of the 65 selected articles, 28 met the inclusion criteria. Conclusion: SARS-CoV-2 is an RNA virus whose protein S is involved in adsorption to the target cell membrane. It is transmitted through contact with contaminated surfaces, secretions or aerosols. In these, it remains viable for three hours, and up to three days on surfaces. Frequent hand washing, disinfecting surfaces, not sharing personal items, social distance of two meters and wearing facemasks when leaving home are recommended. Non-severe patients should be isolated at home for 14 days. Healthcare professionals should use PPE and be careful with potential sources of contamination, including urine and feces of patients during hygiene.